Migration Processes in Indigenous Women Post Internal Armed Conflict in Peru - Velázquez, Tesania; Ruiz Bravo, Patricia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
This paper presents an analysis of the migratory movements of indigenous women in the community of Sacsamarca, Ayacucho, Peru. Based on the qualitative method, life histories and field ethnography were used as sources of data collection. The results indicate that the migration of indigenous women is an Andean community practice, made possible by a network of paisanaje that acts as a facilitating factor. In addition, the findings show that the Internal Armed Conflict (CAI) is a breaking point in the dynamics of the migration processes of Andean communities in Peru and, in the case of these women, it helps to understand the two-way process, since Sacsamarca is a community whose characteristics allow them to return. It is concluded that it is a dynamic process of coming and going, which questions the territorial - geographical - limits of the community and the unidirectional conception of migration.